Potential and limitations of digital ethnographic research: A case study on a web community - Masullo, Giuseppe; Coppola, Marianna (Frontiers in Sociology, 2023)
Introduction This work aims at transposing ethnographic research into digital contexts to probe its potential and limitations in a specific field of study: that of sexuality, particularly suited to ethnographic exploration. We chose as our case study a web community of Italian asexual people. As we shall see, this allowed us to simultaneously explore both the various techniques called into play in digital ethnography and the digital as a specific sphere within which sexuality takes on a very peculiar meaning. Digital sociality is paramount for the definition of imaginaries, meanings, and practices that could not be explored elsewhere. This is due to the implicit characteristics of the population studied, which does not find corresponding physical spaces of aggregation. Methods The paper will present the research design using this specific case study to address some of the typical dilemmas that researchers face when following the digital ethnographic approach and will explore the research results as an example of the kind of analysis available with the information and data collected through this method. Results and discussion The conclusions will attempt to briefly outline the shortfalls and advantages of this method, considering its application to this specific field of study.